Dengue Virus Infections and Maternal Antibody Decay in a Prospective Birth Cohort Study of Vietnamese Infants - Simmons, Cameron (2018)
Dengue hemorrhagic fever can occur in primary dengue virus (DENV) infection of infants. The decay of maternally derived DENV immunoglobulin (Ig) G and the incidence of DENV infection were determined in a prospectively studied cohort of 1244 Vietnamese infants. Higher concentrations of total IgG and DENV-reactive IgG were found in cord plasma relative to maternal plasma. Maternally derived DENV-neutralizing and E protein-reactive IgG titers declined to below measurable levels in >90% of infants by 6 months of age. In contrast, IgG reactive with whole DENV virions persisted until 12 months of age in 20% of infants. Serological surveillance identified 10 infants with asymptomatic DENV infection for an incidence of 1.7 cases per 100 person-years. DENV-neutralizing antibodies remained measurable for > or = 1 year after infection. These results suggest that whereas DENV infection in infants is frequently subclinical, there is a window between 4 and 12 months of age where virion-binding but nonneutralizing IgG could facilitate antibody-dependent enhancement.